The Impact of Communicative Approach on Developing Students` Speaking Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the modern world, significant advancements have been observed in the field of Education, particularly in the teaching of foreign languages. The communicative language teaching approach has become an essential component of English teaching methods and continues to be extensively utilized by foreign language instructors. Additionally, linguists are actively focusing on and studying the topic of communicative language teaching.